The Evaluation of Synergistic Effects of Green Tea and Cinnamon on Antioxidant and Stability of Soybean Oil - Akram Arianfar (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2018)
The aim of the study was comparing antioxidant properties and types of interaction (synergism and antagonism) between green tea and cinnamon extracts. After preparing different extracts, their antioxidant properties were measured by three methods, DPPH, FRAP, and then the ability to prevent the oxidation of soybean oil was tested. BHT was used as positive control for comparison. In this study, phenolic content of the extracts was also determined. Green tea, Cinnamon extracts and BHT were preapared in 25, 50, 100, 150, 200 and 250 µg/ml. The extracts (Green tea: Cinnamon) combined in different ratios (1:1,2:1, 1:2, 1:3, 3:1, 2:2, 1:4 and 4:1). The results of free radical scavenging DPPH, FRAP showed that green tea extract significantly (P<0.05) than cinnamon extract action and both extracts were more effective than the synthetic antioxidant BHT. Combined extracts showed different performance in these tests. Among different combinations of these two extracts, synergisms were found in all combination according to DPPH and free radical scavenging assay. In the peroxide value assay, the combined extracts showed synergism was found in 50 (green tea 25: cinnamon 25). The result shows that it is possible to use these natural antioxidants as substitute of synthetic antioxidant BHT.